Meaning of Islamic Perspective Analogy (Thematic Studies According to Islamic Leaders) - Abdul Saman Nst (Britain International for Academic Research (BIAR) Publisher, 2022)
Regarding the role of analogy in efforts to establish Islamic law, al-Baidawi gives the opinion that analogy is very functional and influential in the formation of Islamic law, when Muslims are faced with a certain case, which cannot be found clearly based on the law of the Qur'an and Hadith. For him, analogy is a method of formulating law that is systematic compared to other methods of conducting ijtihad. In this case, the role of analogy is very dependent on the authority of ijtihad in Islamic law. Using data collection methods through library research, the research also uses several methods including historical methods, content analysis methods, and comparative methods. The historical method is used because the object of study involves the thoughts of a character who lived in the lamp era, which can be known based on his scientific works.